Savage portrayals : race, media, and the Central Park jogger story - Byfield, Natalie P., 1960- (Temple University Press, 2014)
In 1989, the rape and beating of a white female jogger in Central Park made international headlines. Many accounts reported the incident as an example of "wilding"--Episodes of poor, minority youths roaming the streets looking for trouble. Police intent on immediate justice for the victim coerced five African-American and Latino boys to plead guilty. The teenage boys were quickly convicted and imprisoned. Natalie Byfield, who covered the case for the New York Daily News, now revisits the story of the Central Park Five from her perspective as a black female reporter in Savage Port